ALTERNATIVE THERAPY TACTICS: INTEGRATION OF CUPPING THERAPY AND MASSAGE IN MANAGING LOW DENSITY LIPOPROTEIN (LDL) IN HYPERTENSION PATIENTS WITH HYPERCHOLESTEROLEMIA - Lisnawati Lisnawati; Nazaruddin Nazaruddin; Sanatang (Professional Health Journal)
Introduction:Hypertension sufferers with hypercholestrolemia can cause complications from stroke, heart disease and even death. There is a need for a therapeutic approach that can be used by sufferers as an alternative treatment. Objectives:The aim of this research is to analyze the effect of integrating cupping therapy with massage in controlling LDL levels in hypertension sufferers with hypercholetrolemia.